2004
DOI: 10.1007/978-3-540-27864-1_5
|View full text |Cite
|
Sign up to set email alerts
|

Closed and Logical Relations for Over- and Under-Approximation of Powersets

Abstract: Abstract. We redevelop and extend Dams's results on over-and underapproximation with higher-order Galois connections: (1) We show how Galois connections are generated from U-GLB-L-LUBclosed binary relations, and we apply them to lower and upper powerset constructions, which are weaker forms of powerdomains appropriate for abstraction studies.(2) We use the powerset types within a family of logical relations, show when the logical relations preserve U-GLB-L-LUB-closure, and show that simulation is a logical rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Among the attempts of using AI to systematically derive best abstractions, the work of Loiseaux et al [22] and Schmidt [23] are the closest to ours. [22] showed how to derive a simulation-based sound abstract transition system from Galois connections within the AI framework, but their results apply only to the universal fragment of L µ .…”
Section: Application: Abstraction Of Classical Kripke Structuresmentioning
confidence: 85%
See 2 more Smart Citations
“…Among the attempts of using AI to systematically derive best abstractions, the work of Loiseaux et al [22] and Schmidt [23] are the closest to ours. [22] showed how to derive a simulation-based sound abstract transition system from Galois connections within the AI framework, but their results apply only to the universal fragment of L µ .…”
Section: Application: Abstraction Of Classical Kripke Structuresmentioning
confidence: 85%
“…[22] showed how to derive a simulation-based sound abstract transition system from Galois connections within the AI framework, but their results apply only to the universal fragment of L µ . Motivated by the study of MixTSs, [23] showed how to capture over-and underapproximations between transition systems using AI and systematically derived Dams's most precise results. However, the starting goal of this work was formalizing the overand the under-approximations, restricting the result to the specific L µ models, namely, transition systems.…”
Section: Application: Abstraction Of Classical Kripke Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…K 1 ), and then lifted to the merge. Thus, in the merged model, we may have must transitions that are distinct from may transitions because the successors of must transitions are less refined than those of the may transitions (see (Schmidt, 2004), , (Wei et al, 2008)). …”
Section: Computing Mergementioning
confidence: 99%
“…Precision of modal (or mixed) transition systems, with ordinary may and must transitions, is studied in [4,7,21]. They suggest constructions of such abstract models which are most precise among all models from this specific class.…”
Section: Introductionmentioning
confidence: 99%